Immunoglobulins, Mucosal Immunity and Vaccination in Teleost Fish - Yu, Yongyao; Wang, Qingchao; Huang, Zhenyu; Ding, Liguo; Xu, Zhen (Frontiers in Immunology, 2020)
Due to direct contact with aquatic environment, mucosal surfaces of teleost fish are continuously exposed to a vast number of pathogens and also inhabited by high densities of commensal microbiota. The B cells and immunoglobulins within the teleost mucosa-associated lymphoid tissues (MALTs) play key roles in local mucosal adaptive immune responses. So far, three Ig isotypes (i.e., IgM, IgD, and IgT/Z) have been identified from the genomic sequences of different teleost fish species. Moreover, teleost Igs have been reported to elicit mammalian-like mucosal immune response in six MALTs: gut-associated lymphoid tissue (GALT), skin-associated lymphoid tissue (SALT), gill-associated lymphoid tissue (GIALT), nasal-associated lymphoid tissue (NALT), and the recently discovered buccal and pharyngeal MALTs. Critically, analogous to mammalian IgA, teleost IgT represents the most ancient Ab class specialized in mucosal immunity and plays indispensable roles in the clearance of mucosal pathogens and the maintenance of microbiota homeostasis. Given these, this review summarizes the current findings on teleost Igs, MALTs, and their immune responses to pathogenic infection, vaccination and commensal microbiota, with the purpose of facilitating future evaluation and rational design of fish vaccines.